Valores de densidad en la escala de grises en Tomografía Computarizada de Haz Cónico : alcances y limitaciones = Grayscale values in Cone Beam Computed Tomography : scope and limitations - Ruiz Imbert, Ana Cecilia 1983-
Cone-beam computed tomography (CBCT) is a 3D imaging technique widely used in maxillofacial diagnosis. The grayscale value (GSV) is a number that represents the amount of attenuation of the X-ray beam by the material contained in each voxel or structural unit of the tomographic volume. Similarly, in computed tomography (CT) used in medical radiology, the attenuation values are standardized in the Hounsfield Unit (HU) scale. Although GSV may have interesting potential applications in maxillofacial diagnosis, it is essential to know that HU differ from GSV. The latter are susceptible to multiple technical factors during the tomographic acquisition, so their value can vary among different CBCT scanners or when technical parameters are modified. Hence, GSV should not be extrapolated between different CBCT machines, and their use should be cautious while more investigation is available considering various equipment and acquisition protocols.